Metabolomics-constrained modelling reveals dominant oxidative metabolism in the Egyptian fruit bat myocardium - Anja Karlstaedt; Fenn Cullen; Rosie Drinkwater; Zenouska Ramchunder; Kyoungmin Kim; Megan Young; Stephen J. Rossiter; Dunja Aksentijevic (PLoS ONE, 2026)
Aim The present study aimed to elucidate which pathways contribute to cardiometabolic adaptation in Egyptian fruit bats. Methods Utilising cardiac tissues from Egyptian fruit bats ( Rousettus aegyptiacus ) and C57BL/6J mice, we combined liquid chromatography-mass spectrometry metabolic profiling, non-targeted ¹H NMR spectroscopy, and in silico computational modelling using the genome-scale mammalian network CardioNet. By integrating complementary untargeted and targeted metabolomics with genome-scale flux balance analysis, this approach enables systems-level inference of pathway activity beyond static metabolite abundance measurements. Main findings Our analyses revealed that bat hearts exhibit a distinct metabolic profile characterised by depleted glycogen reserves and increased reliance on lipid oxidation to meet energy demands. Notably, bat hearts displayed elevated fluxes in oxidative phosphorylation, β-oxidation of long-chain fatty acids, and the Krebs cycle, alongside reduced amino acid catabolism. These findings suggest that bats have evolved unique metabolic strategies to support the high-energy demands of flight, maintaining cardiac function without succumbing to pathological remodelling. Conclusions This study provides the first comprehensive insight into the metabolic adaptations in the cardiac tissue of a bat species, contributing to our understanding of how these mammals endure extreme physiological stresses.